2005
DOI: 10.1021/ja052522q
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Label-Free Electrochemical Detection and Kinetic Study of Alzheimer's Amyloid Beta Aggregation

Abstract: We present the first electrochemical detection, characterization, and kinetic study of the aggregation of Alzheimer's disease (AD) amyloid beta peptides (Abeta-40, Abeta-42) using three different voltammetric techniques at a glassy carbon electrode (GCE). This method is based on detecting changes in the oxidation signal of tyrosine (Tyr) residue. As the peptides aggregate, there are structure conformational changes, which affect the degree of exposure of Tyr to the molecular surface of the peptides. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(181 citation statements)
references
References 23 publications
12
168
1
Order By: Relevance
“…The parameters of the SWV were the following: initial potential 0.4 V, end potential l.0 V, step potential 4 mV, amplitude 25 mV, and frequency 15 Hz. The results showed tyrosine residue's oxidation peak at approximately 0.71 V, which has been reported in other studies [10]. The results also showed that in the presence of metal ions there is a decrease in the intensity of the current, which led them to the conclusion that Zn (II) and Cu (II) affect the morphology of Ab, aggregation kinetics, and have an impact on the oxidation of the tyrosine residue.…”
Section: Square Wave Voltammetry (Swv)supporting
confidence: 80%
See 1 more Smart Citation
“…The parameters of the SWV were the following: initial potential 0.4 V, end potential l.0 V, step potential 4 mV, amplitude 25 mV, and frequency 15 Hz. The results showed tyrosine residue's oxidation peak at approximately 0.71 V, which has been reported in other studies [10]. The results also showed that in the presence of metal ions there is a decrease in the intensity of the current, which led them to the conclusion that Zn (II) and Cu (II) affect the morphology of Ab, aggregation kinetics, and have an impact on the oxidation of the tyrosine residue.…”
Section: Square Wave Voltammetry (Swv)supporting
confidence: 80%
“…There have been several researches that have used SWV as their main technique of detection, especially in the detection of Ab in the presence of metals [9][10][11]. A study conducted by Hung et al presented the relationship between metal ions like Cu (II), Zn (II) and Fe (II) and the Ab peptide aggregation [9].…”
Section: Square Wave Voltammetry (Swv)mentioning
confidence: 99%
“…In its native form, Ab is unfolded but aggregates into a b-sheet structure of ordered fibrils under various conditions (Stine et al, 2003;Vestergaard et al, 2005). Aggregation is not restricted to pathologically related proteins.…”
Section: Lipid Modulation Of Amyloid Beta Aggregation and Neurotoxicitymentioning
confidence: 99%
“…On the other hand, electrochemical measurements have broad utility, and are easy to fabricate as simple chip devices. Considering the amino acid sequence, Ab has one tyrosine (Tyr) unit at the 10th residue (24), which has a phenol group on the side chain. The phenol group is subject to oxidation, which was utilized to detect Ab on the substrate (Fig.…”
Section: Detection Of Amyloid B Aggregates Using Saccharidementioning
confidence: 99%